The contribution of classroom management and school climate to pjok learning outcomes at madrasah aliyah negeri: systematic literature review - Aldi Ari Saputra; Putra, Aldo Naza; Edwarsyah, Edwarsyah; Syahrial Bakhtiar; Eldawaty, Eldawaty (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
The lack of understanding of how the synergy between classroom management and school climate affects student learning outcomes, especially in PJOK, is the main reason for conducting this study. This study aims to understand how effective classroom management strategies and a positive school climate can affect student engagement, motivation, and achievement in the classroom. This study fills a gap in previous research that has not discussed much about the interaction between the two in depth. Using a systematic literature review, article selection uses a prism flow chart by analyzing studies from journals in the last 10 years from nationally accredited journals and reputable international journals searched on Google Scholar, Mendeley, Science direct.com. The results showed that good classroom management increased student focus, while a supportive school climate encouraged motivation and a sense of belonging. The novelty of this research lies in its approach that highlights the synergy of these two factors in Physical Education. However, this study is limited to the scope of the literature and analysis methods that can affect the generalization of the results. These findings provide insights for educators in creating a more effective learning environment.